Peinture Américaine en Suisse : 1950-1965. - Musée d'art et d'histoire, Genève (Genève : Musée d'Art et d'Histoire, 1976)
Tobey, Mark ; de Kooning, Willem ; Gottlieb, Adolph ; Kline, Franz ; Pollock, Jackson ; Francis, Sam ; Frankenthaler, Helen ; Twombly, Cy ; Rothko, Mark ; Newman, Barnett ; Reinhardt, Ad ; Rauschenberg, Robert ; Rivers, Larry ; Johns, Jasper ; Dine, Jim ; etc.
Peinture Américaine en Suisse : 1950-1965, Musée d'Art et d'Histoire, Genève, 8 Juillet - 4 Octobre 1976
boek